Pancytopenia following rituximab therapy in a patient with rheumatoid arthritis: Could filgrastim be a temporary solution? - Manappallil, Robin George (Asian Journal of Medical Sciences, 2016)
Rheumatoid arthritis is a chronic inflammatory disease affecting the peripheral joints and can also have extraarticular manifestations. The introduction of biological agents have opened new windows to the treatment of rheumatoid arthritis. Rituximab is a monoclonal antibody directed against CD20 cells, thereby reducing the inflammation. There have been reports of neutropenia, but pancytopenia is an uncommon incident. Filgrastim, a human granulocyte colony stimulating factor, can stimulate neutrophil production. The patient being described is a case of rheumatoid arthritis, who developed severe pancytopenia following rituximab therapy. She was given filgrastim injections, which temporarily normalized her leucopenia and neutropenia. This report emphasizes the possibility of developing pancytopenia following rituximab injection and the need of regular follow up of complete blood counts. In such cases, filgrastim may be a temporary solution. Also special consideration should be given to the increased risk of infections after taking rituximab. Asian Journal of Medical Sciences Vol.7(5) 2016 138-141